Management of cases of COVID-19 infection with acute respiratory failure: a narrative review - Alshaer, Omar Rezk; Binobaid, Abdullah Obaid; Saleh, Ruzan Mohammed; Eldabbari, Abdelrahman Abdrabou; Aldawsari, Nasser Ibrahim; Alasmari, Mubarak Mohammed; Alshamry, Abdulkarim Thumail; Almutairi, Aisha Nour; Alluqmani, Musab Salem; Alzahrani, Rayan Saeed; Alqahtani, Mohammed Mana (International Journal Of Community Medicine And Public Health, 2021)
Corona viruses are enveloped, positive-sense, single-stranded large RNA viruses that affect humans and many animals. About 5% of COVID-19 patients need ICU admission due to ARDS, with a case fatality rate varying from 30% to 60%. Some patients need help other than supplementary oxygen, such as non-invasive ventilation or intubation. Before deciding the appropriate respiratory support for acute respiratory failure patients, concerns regarding the dangers of various treatments should be considered. During the treatment of COVID-19 patients, all respiratory therapies face a risk of aerosol-generating procedures. When treating COVID-19 patients, the priority and consideration should be personal safety devices and environmental control/engineering.